Reoxidation of estuarine sediments during simulated resuspension events: Effects on nutrient and trace metal mobilisation. (31st July 2018) - Vidal-Durà, Andrea; Burke, Ian T.; Stewart, Douglas I.; Mortimer, Robert J.G.
Abstract: Estuarine environments are considered to be nutrient buffer systems as they regulate the delivery of nutrients from rivers to the ocean. In the Humber Estuary (UK) seawater and freshwater mixing during tidal cycles leads to the mobilisation of oxic surface sediments (0–1 cm). However, less frequent seasonal events can also mobilise anoxic subsurface (5–10 cm) sediments, which may have further implications for the estuarine geochemistry. A series of batch experiments were carried out on surface and subsurface sediments taken from along the salinity gradient of the Humber Estuary. The aim was to investigate the geochemical processes driving major element (N, Fe, S, and Mn) redox cycling and trace metal behaviour during simulated resuspension events. The magnitude of major nutrient and metal release was significantly greater during the resuspension of outer estuarine sediments rather than from inner estuarine sediments. When comparing resuspension of surface versus subsurface sediment, only the outer estuary experiments showed significant differences in major nutrient behaviour with sediment depth. In general, any ammonium, manganese and trace metals (Cu and Zn) released during the resuspension experiments were rapidly removed from solution as new sorption sites (i.e. Fe/Mn oxyhydroxides) formed. Therefore Humber estuary sediments showed a scavenging capacity for these dissolved species and hence may act as an ultimate sink for these elements. Due to the larger aerial extent of the outer estuary intertidal mudflats in comparison with the inner estuary area, the mobilisation of the outer estuary sediments (more reducing and richer in sulphides and iron) may have a greater impact on the transport and cycling of nutrients and trace metals. Climate change-associated sea level rise combined with an increasing frequency of major storm events in temperate zones, which are more likely to mobilise deeper sediment regions, will impact the nutrient and metal inputs to the coastal waters, and therefore enhance the likelihood of eutrophication in this environment. Graphical abstract: Image 1